Qualitative findings on youths views on the internet and mobile phone: the case of university students in Malaysia - Ramli, Nor Sabila; Hassan, Md. Salleh; Osman, Mohd Nizam; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2014)
The main attempt of this study is to explore the views of youth on internet and mobile phone particularly on the benefits these technologies usage and the problems that emerged from such usage. This is a qualitative study whereby data were gained based on 2 Focus Group Discussions (FGDs). The FGDs were conducted among 2 groups of students of Faculty Modern Language and Communication, Universiti Putra Malaysia. Thematic analysis employed have confirmed most of the youth use both technologies to fulfill their needs on socializing and information and entertainment seeking. In addition to this, some of the youth place their concern on the problem of technology addiction which might worsen if preventive actions are being ignored. A number of discussions and recommendations have been highlighted and expectantly it can assist the concern parties in constructing strategy to further improve internet and mobile phone usage among youth in Malaysia.